El hombre en relación con la creación: una mirada teocéntrica (2020)
This article seeks to reflect on the particularity of human beings regarding other creatures, in relation to a positive interaction with natural entities. First, to reach this objective, we will approach man (image and likeness of God) about the world from a biblical perspective, seeking the deep meaning of some texts that discuss the creation. Second, we will look at man as an active and dynamic agent in the process of fulfilling the world to the Creator himself.